Electronic conductance and thermopower of single-molecule junctions of oligo(phenyleneethynylene) derivatives. Issue 36 (9th September 2020) - Dekkiche, Hervé; Gemma, Andrea; Tabatabaei, Fatemeh; Batsanov, Andrei S.; Niehaus, Thomas; Gotsmann, Bernd; Bryce, Martin R.
Abstract : OPE3 derivatives with tailored substituents are promising substrates for thermoelectric characterization using STM in single-molecule junctions with gold electrodes. Abstract : We report the synthesis and the single-molecule transport properties of three new oligo(phenyleneethynylene) (OPE3) derivatives possessing terminal dihydrobenzo[ b ]thiophene (DHBT) anchoring groups and various core substituents (phenylene, 2, 5-dimethoxyphenylene and 9, 10-anthracenyl). Their electronic conductance and their Seebeck coefficient have been determined using scanning tunneling microscopy-based break junction (STM-BJ) experiments between gold electrodes. The transport properties of the molecular junctions have been modelled using DFT-based computational methods which reveal a specific binding of the sulfur atom of the DHBT anchor to the electrodes. The experimentally determined Seebeck coefficient varies between −7.9 and −11.4 μV K −1 in the series and the negative sign is consistent with charge transport through the LUMO levels of the molecules.